Apigenin, a natural flavonoid, promotes autophagy and ferroptosis in human endometrial carcinoma Ishikawa cells in vitro and in vivo - Yancui Liang; Qian Zhong; Runhui Ma; Zhijing Ni; Kiran Thakur; Jianguo Zhang; Zhaojun Wei (Food Science and Human Wellness)
Apigenin, a natural flavonoid has been reported against a variety of cancer types. However, it is unclear whether apigenin can promote autophagy and ferroptosis in Ishikawa cells. There are few reports on the mechanism of apigenin on autophagy and ferroptosis of endometrial cancer Ishikawa cells. We found that iron accumulation, lipid peroxidation, glutathione consumption, p62, HMOX1, and ferritin were increased, while, solute carrier family 7 member 11 and glutathione peroxidase 4 were decreased. Ferrostatin-1, an iron-death inhibitor could reverse the effects of apigenin in Ishikawa cells. On the other hand, apigenin could promote autophagy via up-regulating Beclin 1, ULK1, ATG5, ATG13, and LC3B and down-regulating AMPK, mTOR, P70S6K, and ATG4. Furthermore, apigenin could inhibit tumor tissue proliferation and restrict tumor growth via ferroptosis in vivo.